Pengaruh Motivasi, Self-Efficacy, Prospek Kerja, Pengetahuan Perpajakan, Nilai Sosial, dan Persepsi terhadap Minat Mahasiswa Jurusan Akuntansi untuk Menjadi Konsultan Pajak - Jason Kosasi; Kazia Laturette (Jurnal Eksplorasi Akuntansi, 2024)
The purpose of this study was to determine what factors influence student’s career choice as a tax consultant. Sampling in this study using purposive sampling method. The sample in this study were Accounting students at Ciputra University Surabaya who had taken taxation courses. The results of this study state that motivation, job prospects, and perceptions positively influence career choice as a tax consultant. Meanwhile, self efficacy, tax knowledge, and social values do not affect career choice as a tax consultant. Future research is expected to add other independent variables and expand the population.